The Relationship Between Supply Environment, Supply Chain Integration and Performance Considering Opportunistic Behaviors - Abbas َAsadi; safanaz Heidari (مدیریت بهره وری)
Abstract: This research was conducted with the aim of examining the relationship among supply environment, supply chain integration, and performance considering opportunistic behaviors. This research employed a goal-oriented approach and utilized a descriptive-correlational design for its data collection procedure. The required data in this study were collected using a questionnaire. The statistical population was all the engineers and managers active in the manufacturing companies located in the industrial town number one of Arak. From among the statistical population of 230 individuals, a sample of 140 participants was obtained using the Cochran sampling method. They were selected through random sampling. The data were analyzed using the Partial Least Squares (PLS) technique, employing SmartPLS software for the analysis. The obtained results showed that there is a significant relationship between supply environment, supply chain integration and performance. However, the mediating role of opportunistic behaviors did not demonstrate a significant relationship, leading to the rejection of the hypothesis.   Key Words: supply environment, supply chain integration, environmental performance, opportunistic behaviors           1.Introduction Waste of resources in a supply chain occurs due to the opportunistic tendencies of its members. Curbing the opportunistic tendencies of influential members who take unfair advantage of weaker organizations helps to reduce the resource consumption of weaker parties in the supply chain. Transaction costs also affect the way organizations interact with each other and cause organizations to show opportunistic behavior in order to maximize their profits. Supply chain integration is based on supply chain management concepts and considers the supply chain as an integrated system. It also focuses on sustainable performance and subsequently includes strategic and executive elements. This view of supply chain performance has led to the emergence of a supply chain management research domain called supply chain orientation. Supply chain orientation is based on the view that the organization's supply chain is an independent entity and focuses on achieving results within the supply chain that lead to better performance. So far, the relationship between supply environment, supply chain integration and performance considering opportunistic behaviors has not been considered. Is there a relationship between supply environment, supply chain integration and performance considering opportunistic behaviors or not? Identifying this relationship will provide an opportunity for future research to consider the effect of supply chain orientation on other supply chain functions and external performance outcomes. Based on this and according to the said contents, the main purpose of this research is to examine the relationship between supply environment, supply chain integration and performance by considering opportunistic behaviors. 2.Literature Review The findings of Nasri Rad's research (2015) showed a positive significant impact of the company's orientations on the sustainability of the supply chain. Among the dimensions of the company's orientation, two dimensions of environmental orientation and cultural orientation had a positive significant effect on sustainable purchasing and sustainable supply procedures. However, the two dimensions of social orientation and regional orientation did not have a significant effect on sustainable purchasing and sustainable supply practices. The results of the data analysis in the research conducted by Mehrabani and Hassanzadeh Farashband (2014) showed that the direction of the supply chain and the relationship management variable with the main supplier have an effect on the effectiveness of organizational purchasing. The results of the structural equation model in the research conducted by Taghizadeh Yazdi and Zulfi (2014) revealed a positive significant causal relationship between supply chain actions and competitive advantage. Also, the direct and indirect relationship between supply chain actions and sustainability was confirmed. Li and Nam (2016) showed in their research that organizational supply chain orientation has a significant effect on supply chain management and that it is also affected by management supply chain orientation. On the other hand, operational supply chain management is only affected by supply chain orientation information technology. Structural supply chain orientation also moderates the role of strategic supply chain orientation in meeting customer needs. Luzini (2015) demonstrated in his research that supply chain collaboration improves business performance; the market, performance, value and cooperation of the supply chain positively affects the financial performance; and the cooperation capabilities between companies have a positive significant impact on the company's business performance. Also, the cooperation of upstream and downstream members of the chain can support different forms of business. In their study, Esper et al. (2010) showed that the strategy and orientation of the structural supply chain can be effective in realizing the organization's goal of increasing organizational advantages. Finally, Gold et al. (2010), in their study, revealed that the strategic and structural dimensions of supply chain orientation help to improve supply chain cooperation and its combined effect is greater especially in uncertain dynamic environments. 3.Methodology The methodology employed in this research is grounded in applied research principles. The purpose of this research was to test theoretical concepts in real-world situations and address practical problems to improve the processes or products. The statistical population of the present study consisted of all the engineers and managers active in the manufacturing companies located in the industrial town of Arak, 140 of whom were selected as the sample of the study through available sampling. The current research has two distinct phases in the data collection and analysis. In the first phase, the data was analyzed using descriptive and inferential statistics methods. In descriptive statistics, mean, standard deviation and frequency tables are used. Then, inferential statistics are employed to explain the relationships between variables and generalize the results to the society. Cronbach's alpha test is used to determine reliability, and Lisrel software and structural equation model are used to confirm or reject each hypothesis. 4.Result Initially, library studies were used to review the necessary theoretical literature in the field under investigation and then, the information needed for this research was collected through a questionnaire. The statistical population of the current research was all the engineers and managers active in the manufacturing companies located in the industrial town of Arak. Form among the statistical population of 230 individuals, a sample equal to 140 participants was recruited through random sampling. To analyze the data, partial least squares technique was used, employing SmartPLS software. The obtained results showed that there is a significant relationship between supply environment, supply chain integration and performance. However, the mediating role of opportunistic behaviors was rejected. This hypothesis was composed of some sub-hypotheses.  The results obtained for testing each of these sub-hypotheses are as follows: The results obtained from the t-statistic at the rate of 9.193 showed that there is a significant relationship between the supply environment and the integrity of the supply chain; the results obtained from the statistic t at the rate of 8.094 showed that there is a significant relationship between supply chain integration and productivity; the results obtained from the t statistic at the rate of 23.703 revealed that operational profit has a significant relationship with environmental performance; and the results obtained from the t-statistic at the rate of 1.118 rejected the mediating role of opportunistic behaviors within the work environment regarding the influence of supply chain integration on operational productivity. 5.Discussion In a supply chain, waste of resources arises from the opportunistic tendencies of its members. By curbing the opportunistic tendencies of influential members who exploit unfair advantages over weaker organizations helps to reduce the resource consumption of weaker parties in the supply chain. Therefore, it is suggested that industries, after adopting the appropriate supply chain strategy, in order to examine the correctness of this strategy and achieve the goals corresponding to that strategy, seek integration in the supply chain of their organization and its development. By holding training courses, managers and officials should increase the chain members' knowledge about the factors affecting the supply chain management of the project to enhance operational efficiency. This can be achieved by outlining a series of actions related to social responsibility towards the environment and employees, which may include: increased attention and investment in training employees focusing on skill development and behavioral improvement, determining rewards and welfare facilities appropriate to the performance of employees, career development and the possibility of promotion at all organizational levels, equality and job justice at all organizational levels, involving employees in decision-making, creating a cheerful, clean and safe environment for employees, and improving productivity and accordingly, performance in this environment.